Analysis of Students' Mathematical Communication Ability on Set Materials Based on Gender Differences - Rodhitul Amni (Journal of Research on Mathematics Instruction (JRMI), 2021)
The study was conducted to determine the students’ mathematical communication skills in the set material. In doing math problems, there are still many students who make mistakes in solving the questions given by the teacher. Students' difficulty in answering questions, one of which is influenced by mathematical communication skills. The method used is descriptive qualitative, which is analyzed from the instrument in the form of 5 written test questions in the form of description questions. The subjects studied were 22 students. This research was conducted on Thursday, October 21st 2021, at Madrasah Tsanawiyah Al Muhajrin Tapung, 2021/2022, totalling 13 female and nine male students. In this study, there are three indicators used, namely 1) mathematical expressions, which are everyday events that are expressed in mathematical concepts and mathematical symbols, 2) drawing, which is mathematical ideas that can be expressed in terms of mathematical concepts. In the form of pictures, and 3) writing (written text) that can show and explain everyday events into mathematical models and mathematical language. From the results of mathematical communication skills based on gender with these three indicators, female students have higher mathematical communication skills than male students. The average percentage for female students is 70.8%, and the percentage of male students is 52.75%. The results of the conversion of scores in the very low category for male students and medium category for female students.